2011
DOI: 10.1155/2011/506171
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol‐Rich Fraction Prevents Cell Cycle Arrest and Elongates Telomere Length in Senescent Human Diploid Fibroblasts

Abstract: This study determined the molecular mechanisms of tocotrienol-rich fraction (TRF) in preventing cellular senescence of human diploid fibroblasts (HDFs). Primary culture of HDFs at various passages were incubated with 0.5 mg/mL TRF for 24 h. Telomere shortening with decreased telomerase activity was observed in senescent HDFs while the levels of damaged DNA and number of cells in G0/G1 phase were increased and S phase cells were decreased. Incubation with TRF reversed the morphology of senescent HDFs to resembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 39 publications
5
51
1
1
Order By: Relevance
“…Herein, we can propose that H 2 O 2 induced senescence in NIH3T3 cells through the initiation of OS, ROS formation, and overexpression of inflammatory cytokines. 56,57 In molecular viewpoint, the accumulation of OS (in this case H 2 O 2 ) induces p53-dependent apoptosis, resulting in cells passage to G1 and undergo arrest. Furthermore, OS activates cellular inflammatory responses that are generally controlled by the transcription factor NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we can propose that H 2 O 2 induced senescence in NIH3T3 cells through the initiation of OS, ROS formation, and overexpression of inflammatory cytokines. 56,57 In molecular viewpoint, the accumulation of OS (in this case H 2 O 2 ) induces p53-dependent apoptosis, resulting in cells passage to G1 and undergo arrest. Furthermore, OS activates cellular inflammatory responses that are generally controlled by the transcription factor NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that antioxidants can prevent the oxidation of various macromolecules, such as DNA, proteins, and lipids, thus preventing the aging process and increasing the lifespan of the organism (13,14). In this study, we investigated three types of antioxidants: Piper betle (PB), the tocotrienol-rich fraction (TRF), and Chlorella vulgaris (CV).…”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols are saturated forms of vitamin E, and tocotrienols are the unsaturated forms, distinguishable by the three double bonds in the tails of tocotrienols (7). Studies showed that tocotrienol is superior for its antioxidant properties as well as increasing cells viability and proliferation (8,9). The current project aim to evaluate the response of human periodontal ligament fibroblasts (HPdLF) upon exposure to various concentrations of tocotrienols rich fraction (TRF) conditioned medium.…”
Section: Introductionmentioning
confidence: 99%